When Indonesia Comedians Talked about Omnibus Law: Pragmatically Comprehension - Fithrah Auliya Ansar; Darwissyah Irwan Duhir (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
This research aims to understand the message and the way of comedians in delivering their messages toward omnibus law in Indonesia. How the comedians build their power through language to confirm their position. Pragmatics analysis was a main tool in analyzing the language used by comedians. This research observes two videos of different comedians commenting the law through social media. Both videos examine the truth of comedians’ voice on Omnibus law. The comedians absolutely have their special characteristic in reflecting their ideology towards the regulation. Their position reflected from the speech that supporting the demonstrators against omnibus law validation. The result shows that both comedians used some features such as irony, metaphors, and satires in criticizing the government. Plethora signs are given by them in comparing the power and effectiveness of previous and current government in coping country’s problems. Moreover, there are several pragmatics cues used to inform people about their position in facing the government’s policy.